Incidence of shoulder functional morbidity following ipsilateral mastectomy and latissimus dorsi flap reconstruction - Muhammad Umar; Noman Jahangir; Michael Hughes; Qasim Malik; Jalal Kokan; M. Waseem (Acta Orthopaedica et Traumatologica Turcica, 2019)
Introduction: The aim of this study was to investigate the incidence of shoulder morbidity in our cohort of patients with latissimus dorsi flap reconstruction after mastectomy. Methods: This is a retrospective study of prospectively collected data of 72 patients using validate Oxford shoulder score for function and quickDASH score for disability. Scores were collected preoperatively and at time of final review or study. We also reviewed patient records for patients who had a formal diagnosis of shoulder pathology. Results were analysed with student t-test. Results: Analysis of scores showed a statistically significant worsening of both oxford shoulder score (p < 0.005) and quickDASH score (p < 0.005), when pre and post-operative scores were compared. Seven patients had a formal diagnosis of shoulder pathology, and all of them recovered well. There was no significant difference in oxford shoulder score or quickDASH scores between patients with or without shoulder pathology. About 40% patients had some functional loss or disability at 4 years after the surgery. Conclusion: Our study shows a high incidence of significant shoulder functional morbidity following latissimus dorsi flap reconstruction but number of patients requiring specific treatment is low. Level of evidence: Level IV, therapeutic study. Keywords: Mastectomy, Reconstruction, Latissimus dorsi flap, Breast cancer, Shoulder morbidity